The Concept of Al-Ṭhahur in the Qur’an: A Semantic Analysis from Toshihiko Izutsu’s Perspective - Ahda Sabila; Andri Nirwana AN; Kharis Nugroho; Sufian Suri; Muhammad Ndow (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This research aims to explore the core meaning, semantic relationships, and conceptual scope of al-Thahur (purity) in the Qur’an, encompassing both physical and spiritual dimensions. Theoretical framework: This study adopts the semantic approach of Toshihiko Izutsu to analyze the concept of al-Thahur in the Qur'an, focusing on the relationships between words and their meanings in the sacred text. Literature review: Previous studies have explored the concept of purity in Islam, often focusing on physical purity through ritual acts such as ablution and purification from impurity. However, fewer studies have investigated the spiritual dimensions of al-Thahur, which includes purification from sin, disbelief, and immoral traits. This research aims to fill this gap by examining both the physical and spiritual aspects of purity as presented in the Qur'an. Methods: A semantic analysis approach is employed, involving the collection of verses that mention the term al-Thahur. The analysis covers the context of these verses, syntagmatic and paradigmatic relationships, and interpretation based on classical and contemporary tafsir literature, as well as linguistic references. Results: The study finds that al-Thahur in the Qur’an extends beyond physical purity, such as cleansing from hadas and najis, to include spiritual purity, such as the purification of the soul from sin, polytheism, and immoral behavior. The concept is used in various contexts, including self-purification through worship, cleansing the heart from doubts, and the purification of faith. Implications: This research highlights the holistic nature of purity in Islam, linking physical cleanliness with moral and spiritual integrity. The findings underscore the importance of al-Thahur as a foundational concept in Islamic teachings, guiding not only ritualistic practices but also personal morality and spirituality. Novelty: The novelty of this study lies in its comprehensive analysis of al-Thahur from both physical and spiritual perspectives, using a semantic approach to uncover deeper insights into the Qur'anic concept of purity. This research bridges the gap between physical cleanliness and spiritual integrity in the understanding of purity within Islamic teachings.